Data Bases available through APIs using Restify: Characteristics, Programming Models, and Benchmarks - Marques, Luiz F. [UNESP]; Correia, Ronaldo C. M. [UNESP]; Spadon, Gabriel [UNESP]; Eler, Danilo M. [UNESP]; Olivete-, Celso [UNESP]; Garcia, Rogerio E. [UNESP]; IEEE (Ieee, 2017)
The volume of data exchanged by computer networks is gradually increasing over time, which provides the need for performance and interoperability between different platforms and systems. In this line, there are several studies dedicated to service-oriented software architectures and resource consumption models. However, a few of them are focused on the development of generic tools for the dynamic creation of data provisioning services. This article presents the analysis of a tool called Restify, which is able to dynamically create web services to provide an online database as a service. Restify achieved the system interoperability requirements regarding heterogeneous operations, programming languages, and server infrastructures. As a result, we observed that the performance of this tool was comparable, if not better, than other evaluated web services, such as REST and SOAP. Finally, Restify excels by behaving like an interface tool, allowing the management and integration of multiple online system tools with various relational databases.
Keywords: Web Service; REST; Database as a Service